Run-on and Fragment Sentences: An Error Analysis in Indonesian English Learners’ Writings - Shilva Lioni; Zulprianto Zulprianto; Dhiant Asri; Iman Sagito; Novia Irene Zendrato (Vivid: Journal of Language and Literature, 2022)
Run-on and fragment sentences provide clues as to how English learners understand English sentences and how English learners organize information and shape their essays. This research was based on a group case study of run-on and fragment sentences in English college students’ essays, using an English Sentence Completeness approach to investigate how English college students make an error on making a sentence in their English essays and discusses the further pedagogical implications based on the errors pattern found. English college students were found to do run-on in their sentences more often than fragments. They write more than one subject and one verb in a sentence and significantly forget to limit their sentences. The carelessness in punctuation and a period between sentences make the sentence permitted to “run on” into the next. Besides run-on, fragments were also found in students’ essays: Missing subject and verb conditions are significantly found in the students’ sentences. These findings revealed that English college students lack knowledge of how to make complete sentences in ordering information and building up a text’s structure. Therefore the learning process of English writing should be informed of the importance of English sentence completeness in organizing a text and introduce the strategies for avoiding and making less run-on and fragment sentences through practice activities and writing assignments. This research is qualitative descriptive-explorative research where descriptive and explorative are intended to describe and explain the situation based on collected data and facts, which are then analyzed and arranged systematically to get conclusions in detail to be a hypothesis.